Ekonomia polityczna procesu integracji polskiego rolnictwa z Unią Europejską - Zawojska, Aldona (Political Economy of the Process of Polish Agriculture Integration with the European Union, 2005)
The paper concerns the influence of social and political forces on the integration of Polish agriculture with the EU in the framework of the Common Agricultural Policy. The author presents the main arguments against the current system of farm support within the EU as well as the distributional effects of this policy.The process of the integration in the field of agriculture raises fundamental issues of efficiency and equity. The CAP imposes a cost on consumers through higher food prices, on taxpayers through higher taxes, and on all society through negative externalities. Additionally, the CAP is a good example of government failure. The biggest beneficiaries of the CAP are the most affluent farmers and different interest groups.Despite this, the support of Poles, including farmers, for the EU's membership of Poland is increasing. Generally, Polish farmers are considered to be winners of the CAP. It is difficult to believe that self-interested politicians, farm organisations and lobby will be concerned in changing the status quo. Moreover, the history of the CAP reform shows that shortcomings in agriculture policy have not been sufficient to bring about the reform.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 452-459